2007
DOI: 10.3892/ijmm.19.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Fibrotic response to angiotensin II is blunted in the kidney, but not in the heart, in insulin-sensitive long-lived transgenic dwarf rats

Abstract: Abstract. Insulin resistance is a characteristic feature of cardiovascular and renal diseases, and angiotensin II (Ang II) has been suggested to induce insulin resistance. The aims of this study were to elucidate the effect of chronic Ang II infusion on vascular reactivity and organ damage in insulinsensitive rats. We confirmed the following three points. First, there was no significant difference in pressor response to chronic Ang II infusion (600 ng/kg/min) between insulinsensitive transgenic rats (Tg) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…As a potential explanation, TGF-β is a strong inducer of PAI-1 expression 26. A previous study reported that the molecular mechanism involves tissue-specific TGF-β response to Ang II infusion; hence the PAI-1 response to TGF-β can display tissue-specific characteristics 27…”
Section: Discussionmentioning
confidence: 99%
“…As a potential explanation, TGF-β is a strong inducer of PAI-1 expression 26. A previous study reported that the molecular mechanism involves tissue-specific TGF-β response to Ang II infusion; hence the PAI-1 response to TGF-β can display tissue-specific characteristics 27…”
Section: Discussionmentioning
confidence: 99%